Best Answer

The simplify of 2 times 2 take away 2 equals 2. This is a math problem.

Study guides

☆☆

Q: Simplify the given expression 2x 2 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

The given expression can be simplified to: 2x-2

In algebra collect like terms means combining the like terms together. It can be done with the help of variables, powers and the terms which have like properties. When collecting like terms the corresponding sign of a particular number will carry with the term.For Example:Combine the like terms and simplify the expression 2x + 8y +2 + 4x + y + 1SOLUTION:The given expression is 2x + 8y +2 + 4x + y + 1The terms in the given expression is 2x, 8y, 2 , 4x, y, 1.Now combine the like terms with the help of variables.Collect 2x and 4x together, 8y and y together and the constants 2 and 1 together.The simplified answer for the given expression is= 2x + 8y +2 + 4x + y + 1= 2x+4x +8y +y + 2+1= 6x + 9y +3

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

3 + 3 + 2x = 0 6 + 2x = 0 2x = -6 x = -6/2 x = -3

Related questions

The simplest form of 2 times 2 take 2 equals 2. his is taught in math class.

It can be factored as 18(5-2x^2)

The given expression can be simplified to: 2x-2

The given expression can be simplified to: 2x-2

In algebra collect like terms means combining the like terms together. It can be done with the help of variables, powers and the terms which have like properties. When collecting like terms the corresponding sign of a particular number will carry with the term.For Example:Combine the like terms and simplify the expression 2x + 8y +2 + 4x + y + 1SOLUTION:The given expression is 2x + 8y +2 + 4x + y + 1The terms in the given expression is 2x, 8y, 2 , 4x, y, 1.Now combine the like terms with the help of variables.Collect 2x and 4x together, 8y and y together and the constants 2 and 1 together.The simplified answer for the given expression is= 2x + 8y +2 + 4x + y + 1= 2x+4x +8y +y + 2+1= 6x + 9y +3

The given expression can be simplified to: 2x-2

2X divided by 4= 2X

1

2x + 2 is an algebraic expression. It is also a polynomial and it has two terms: 2x and 2.

10

I assume you wish to simplify the expression (x - 2)/(3x + 9) . (2x + 6)/(2x - 4) = (x - 2)(2x + 6) / [(3x + 9)(2x - 4)] = 2(x - 2)(x + 3) / [6(x + 3)(x - 2)] = 1/3.

6x^2